2013
DOI: 10.1016/j.celrep.2013.07.046
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Methyltransferase Dnmt2 Is Required for Efficient Dicer-2-Dependent siRNA Pathway Activity in Drosophila

Abstract: Transfer RNA (tRNA) fragmentation in response to stress conditions has been described in many organisms. tRNA fragments have been found in association with small interfering RNA (siRNA) components, but the biological role of these interactions remains unclear. We report here that the tRNA methyltransferase Dnmt2 is essential for efficient Dicer-2 (Dcr-2) function in Drosophila. Using small RNA (sRNA) sequencing, we confirmed that Dnmt2 limits the extent of tRNA fragmentation during the heat-shock response. tRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 27 publications
4
108
0
Order By: Relevance
“…It was shown that tRNA halves may not only regulate translation, but also small RNA homeostasis during heat-shock. 53 Increased tRNA cleavage, induced by decreased tRNA stability (e.g., under certain stress conditions or lacking methylation in the anticodon loop), seems to interfere with the small-interfering RNA (siRNA) pathway through binding of tRNA halves to Dicer-2 ( Fig. 1).…”
Section: Trna In Piecesmentioning
confidence: 99%
“…It was shown that tRNA halves may not only regulate translation, but also small RNA homeostasis during heat-shock. 53 Increased tRNA cleavage, induced by decreased tRNA stability (e.g., under certain stress conditions or lacking methylation in the anticodon loop), seems to interfere with the small-interfering RNA (siRNA) pathway through binding of tRNA halves to Dicer-2 ( Fig. 1).…”
Section: Trna In Piecesmentioning
confidence: 99%
“…Increased tRNA cleavage during heat shock in flies lacking the Dnmt2 modification enzyme has been shown to interfere with the siRNA pathway. tiRNAs bind to Dicer and saturate its binding pocket, thus reducing its ability to cleave dsRNAs (31). In an alternative mechanism, tRFs serve as substrates for the cellular RNAi machinery.…”
Section: Role Of Tirnas In the Cellular Stress Response And Other Patmentioning
confidence: 99%
“…53 Similarly, TRDMT1 mutant flies contain stress induced tRNA fragments and constitutively upregulate the innate immune system. 57,58 …”
Section: 38mentioning
confidence: 99%